An assessment of the capability of five selected municipal planning and development offices in the Province of Aklan - Calimpong, Rowena; Ruiz, Deana G.; Teofilo, Catherine R.; Samagaysay, Jonas (1999)
This study was conducted in the months of April to June 1999, inclusive and consisted of two (2) parts ; Organizational and performance. Both organizational and performance study covered five (5) selected Municipal Planning and development Offices in the Province of Aklan namely : banga, Kalibo Lezo, New Washington and Numancia. It used a survey questionnaire for primary data collection, on-site interview for data validation, and interview guides for the performance evaluation. It aimed at determining and assessing the characteristics of MPDO personnel and physical facilities. Also, it aimed at establishing the relationship of the personel and physical resources, or office capability, with office performance as indicated by : productivity, efficiency, effectiveness, responsiveness and timeliness. The five (5) MPDOs had a composite of 24 employees, 21 permanent, 1 temporary and 2 casuals.. Average number of employees was 4.2 permanent personnel per office. These occupied varied positions, 5 of which were MPDCs. They possessed the educational competence to perform office fubctions. Trainings attended averaged 3.2 training areas per office. Physical offices were available to all although others shared with other offices. Communication facilities were available to 3 MPDOs, 2 with telephonea and 1 withhandsets. One MPDO had four-wheel vehicle and 4 MPDOs have motorcycles as transportation support. Office capability being indicated by the composite of personnel (number, education, and training), office and equipment, communication facilities and traansportation support. performance was indicated by productivity, responsiveness and timeliness in delivery of rural development programs/services as further indicated by : number of programs/projects implemented, average number of needs responded to by programs/projects, planning documents on-file, methods of techno-transfer, and direct assessment of key informants.
[Research Paper] (PM 299-Research Methods and Applications). -- Iloilo City : UPV-CM, June 1999.